Generation of nutrients and detoxification: Possible roles of yeasts in leaf-cutting ant nests - Mendes, Thais D.; Rodrigues, André [UNESP]; Dayo-Owoyemi, Ifeloju [UNESP]; Marson, Fernando A.L. [UNESP]; Pagnocca, Fernando C. [UNESP] (MDPI, 2012)
The possible roles played by yeasts in attine ant nests are mostly unknown. Here we present our investigations on the plant polysaccharide degradation profile of 82 yeasts isolated from fungus gardens of Atta and Acromyrmex species to demonstrate that yeasts found in ant nests may play the role of making nutrients readily available throughout the garden and detoxification of compounds that may be deleterious to the ants and their fungal cultivar. Among the yeasts screened, 65% exhibited cellulolytic enzymes, 44% exhibited pectinolytic activity while 27% and 17% possess enzyme systems for the degradation of protease and amylase, respectively. Galacturonic acid, which had been reported in previous work to be poorly assimilated by the ant fungus and also to have a negative effect on ants' survival, was assimilated by 64% and 79% of yeasts isolated from nests of A. texana and Acromyrmex respectively. Our results suggest that yeasts found in ant nests may participate in generation of nutrients and removal of potentially toxic compounds, thereby contributing to the stability of the complex microbiota found in the leaf-cutting ant nests. © 2012 by the authors; licensee MDPI, Basel, Switzerland.
Keywords: Attini; Fungi; Metabolism; Polysaccharidases